Popular music, popular myth and cultural heritage in Cleveland : the Moondog, the Buzzard, and the battle for the Rock and Roll Hall of Fame - Lashua, Brett (Emerald studies in popular music and place, 2019)
This book presents a case study of popular music heritage to address why, and how, Cleveland, Ohio has claimed to be the ""birthplace of rock 'n' roll"" and became the home of the Rock and Roll Hall of Fame. It explores the role of radio DJs, record stores, concerts and myths in shaping the relations between people, places, and the past.